Effectiveness of influenza vaccine in reducing hospital admissions during the 1989-90 epidemic. - Ahmed, A. H. (1997)
The effectiveness of influenza vaccine in reducing hospital admissions for pneumonia, influenza, bronchitis, or emphysema was assessed by a case-control study of people aged 16 years and older who were admitted to 10 Leicestershire hospitals between 1 December 1989 and 31 January 1990. Hospital and general practitioners' records for 156 admissions (the cases) and 289 controls matched for age and sex were reviewed. Information was collected on demography, the usual place of residence (institutional or non-institutional), the existence of chronic illness, and vaccination during the 5 years before admission. The odds ratio for hospital admission among vaccinees was 0.67 (95% CI 0.39-1.12) giving an estimate of vaccine effectiveness in this setting of 33% (95% CI 0-61). However, multivariate logistic regression, adjusting for the effects of institutional care and chronic illness, revealed that influenza vaccination reduced hospital admissions by 63% (95% CI 17-84%). There was a strong trend towards improved vaccine effectiveness when used in institutional settings. Influenza vaccine is effective in reducing hospital admissions for influenza, pneumonia, bronchitis and emphysema, and effectiveness is comparable to that observed for influenza and pneumonia admissions in North America.